IDENTIFIKASI HAK KEKAYAAN INTELEKTUAL, PENGETAHUAN TRADISIONAL DAN EKSPRESI BUDAYA TRADISIONAL (PTEBT) LURIK KLATEN - Pratomo, Sigit Adhi; Dharmo, Pujo; Sulistyowatie, Syska Lady; Sulistyowati, Istri; Nasrulloh, Rifqi Syarif (Economic Faculty, Attahiriyah Islamic University, 2020)
Purpose- This research aims to: (1) examine the activities of the center and community (community) carriers of lurik Klaten; (2) To thoroughly examine the PTEBT lurik Klaten; and (3) Identifying IPR documents at the Klaten lurik center. Design/methodology/approach- Qualitative research methods with a juridical empirical approach or legal sociology. Findings- The research results show that the documentation system for standard lurik motifs is still incomplete and there is a lack of knowledge of traditional craftsmen on lurik production. Implication- It is necessary to pay attention to the intellectual property rights of the craftsmen for the copyright of the creation of new motifs from each lurik craftsman, this is aimed at avoiding imitation / counterfeiting of lurik motifs. Keywords: Intellectual Property Rights, Traditional Knowledge, Traditional Cultural Expressions